Sharia Enterprise Theory sebagai Basis Optimalisasi Produksi dan Pendapatan Petani Padi: Sharia Enterprise Theory as a Basis for Optimizing Production and Farmers’ Income in Rice Cultivation - Didik Wahono; Anisa Kusumawardani (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: The aim of this study is to determine the extent to which optimization of capital, technology and labor affects the level of farmer income through the role of Islamic economic principles. Design/methodology/approach: This study used a quantitative data collection method, namely purposive random sampling with the Solvin formula approach. The population used was rice farmers in Jati District, Blora Regency, Central Java, using primary data of 11,625. From the total population, 387 samples were taken. Findings: Optimizing capital and labor has a significant positive impact on rice farmers' income levels. However, technology has no effect on rice farmers' income levels. Research implications: From the results of this research, it is necessary for rice farmers to take action to improve technology because by keeping up with the times, the agricultural system will also develop by utilizing developments in digital science.